Construction workforce management in the fourth industrial revolution era - Aghimien, Lerato; Aigbavboa, Clintin Ohis; Aghimien, Douglas (Emerald Publishing Limited, 2024)
The construction industry is a huge employer all over the world, but due to the project-based nature of construction, opportunities to improve pay, conditions and use of technology are often overlooked. The lack of attention to workforce management issues in the construction industry contributes to its overall poor performance in most countries worldwide. To address this problem, it is necessary to understand the practices that need to be in place for construction organisations to be able to manage their workforce effectively. Construction Workforce Management in the Fourth Industrial Revolution Era explores the concept of workforce management in construction and the impact of the pervasive technologies offered by the fourth industrial revolution on the effective management of the construction workforce. Through a critical review of existing related theories and models, gaps in existing workforce management studies are unearthed, and a conceptual model designed to improve the management of workers in the construction industry is proposed. The content here benefits researchers seeking to expand the frontiers of knowledge on workforce management in construction.